New Zealand 20th century sea level rise: Resolving the vertical land motion using space geodetic and geological data. Issue 11 (15th November 2013) - Fadil, Abdelali; Denys, Paul; Tenzer, Robert; Grenfell, Hugh R.; Willis, Pascal
<x xml:space="preserve">Abstract</x> [1] Investigations in long‐term instrumental tidal records reveal that 20th century sea level along the coast of New Zealand is rising at 1.46 ± 0.10 mm/yr in agreement with the regional rates from southern Australia and Tasmania. We extend the advanced altimeter‐gauge approach of combining satellite altimetry and tide gauge data with constraint equations from long‐term adjacent tide gauge records to assess its performance in open seas and to explore the impact of vertical land motion on the observed relative sea level. This approach has again proven to be a robust method with an accuracy of 0.4 mm/yr. While no clear sea level rise pattern can be inferred once the tide gauge apparent sea level trends are corrected for vertical land motions from GPS, the advanced altimeter‐gauge and geological vertical rates are completely consistent and reveal three temporal phases of sea level rise marked by an increase from 1.46 ± 0.10 mm/yr to 1.72 ± 0.10 mm/yr during the period (1900–1936), followed by a decrease to 1.48 ± 0.10 mm/yr during the period (1936–1956), and a substantial increase to 2.60 ± 0.10 mm/yr during the period (1956–1975). In contrast, the 20th century microfossil proxy records of absolute sea level rise display twice the tide gauge sea level rise rate of 3.17 ± 0.30 mm/yr and 3.28 ± 0.45 mm/yr, respectively, once salt‐marsh records are corrected using GPS and geological vertical rates. Differential autocompaction and transfer functions are possible factors, which need further investigation.